Personal resources conducive to educational success: high achieving students' perspectives - Jolise 't Mannetje; Marjolein Heijne-Penninga; Nicole Mastenbroek; Marca Wolfensberger; Debbie Jaarsma (Hanze UAS, 2021)
This study was explorative and aimed at in-depth understanding of personal resources students use to reach success, in the demanding context of honours education.   Becoming successful in higher education demands a lot from students. Considering the Job Demands-Resources model it is expected that personal resources help students succeed. We explore which personal resources benefit students' performance in demanding contexts of honours education. Using a questionnaire and semi-structured interviews, we asked thirteen honours students of three institutions which personal resources had helped them to achieve success. Results suggest that honours students use different personal resources. Most frequently mentioned resources could be grouped around five themes: self-directiveness, inquiry-mindedness, perseverance, social involvement and motivation. Especially resources in the themes self-directiveness, inquiry-mindedness and perseverance were perceived as important facilitators for educational success. The outcomes may inform interventions to help students develop personal resources needed to handle high educational demands. Further research is needed to identify the most effective interventions.